‘Ināyat al-Muḥaddithīn al-Indūnīsiyyīn bi al-Arba’īniyyāt; Dirāsah ‘an Kitāb al-Fādānī fī al-Arba’īn - Daud Rasyid Harun (JOURNAL OF QUR'AN AND HADITH STUDIES, 2020)
This article discusses one of the works of hadīth scholar, which is known as “Arba`īn”. The writers of Arba`īn collect forty hadīths from different topics and then combined them into one book.  Some of them innovated in combining the hadīth. This type of work is known as “Arba`ūn Buldāniyah”. The first scholar to do this is al-Ḥāfiẓ Abū Ṭāhir as-Silafi, then followed by his student, Ibnu `Asākir. Shaikh Yāsīn, a Hadīth scholar from Indonesia who lived in Mecca since he was child. Shaikh Yāsīn had a good reputation in Isnād (chain of hadīths) by maintaining the continuous line of transmission from his teacher, the teachers of his teacher, and to the author of the book studied, as was done by previous scholars.  He contributed to the writing of An Arba`īn book which contained forty hadīth from forty scholars (teachers) from forty cities in the Islamic world. This paper discusses the writing method of the book and compares it with works such as from other authors. The methodology used is a qualitative method by analyzing the works of Islamic scholars. The findings in this paper are that Islamic scholars. are comparable to Middle Eastern scholar in producing even specific Hadith scientific works.